A problemática da sucessão em empresas familiares e a instrumentalização da governança corporativa: um estudo de caso - Matesco, Karen (2014)
This research intends to study the family succession issues, what is normally considered the worst moment In the lives of family business Since companies strength’s in family ones are related to founder personal aspects, when he or she is left the company, many times, fails. Sometimes the family succession occurs at the same time of professionalizing need issues. To face these challenging moments, Corporate Governance is presented as a possible framework and will be study in this paper.